STUDI KEANEKARAGAMAN JENIS BURUNG DIURNAL DI SEKSI PENGELOLAAN TAMAN NASIONAL (SPTN) WILAYAH III SELIMBAU TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU PROVINSI KALIMANTAN BARAT - Harmoko, Eko Puji; Erianto, .; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2018)
This study aims to determine the diversity of bird species diurnal contained in the  Danau Sentarum National Park  Kapuas Hulu so that later can provide information about the diversity of bird species diurnal in Danau Sentarum National Park  and can be used as basic data for the management and development in an effort preservation and protection. This research was conducted by field observation techniques using the track combined with the point count method. Observations were made on three different habitats that secondary forest habitat with three lines of observation, non-forest habitat observation and three lines three lines of observation of aquatic habitats, where each site is done three replications. Observations made with each path length of 1,000 m and width of track 100 m (50 m 50 m left and right). The results showed that from the three habitat study found 76 species of diurnal birds , which consists of 42 species in the habitat of secondary forests with a total of 394 individuals, habitat non forest 49 species with a total of 256 individuals and 31 species in aquatic habitats with the number of individual 590, From the 76 species of birds found there are 38 species of diurnal birds are included in the list of protected species according to the IUCN, CITES and PP No.7 of 1999 concerning Preservation of Plants and Wildlife. ie IUCN there are 12 kinds, there are 12 kinds CITES and PP 7, 1999 there are 22 species of birds.Keyword: Diurnal birds, species diversity, track method.